KORELASI GAYA HIDUP SEHAT DENGAN PRESTASI AKADEMIK MAHASISWA KEPERAWATAN - Sandehang, Cornelia Fransiska; Sada, Fidy Randy; Palenewen, Lucky Albertus; Lamonge, Annastasia Sintia; Budiawan, Helly (Ensiklopedia of Journal, 2025)
Abstract:  One of the factors that can affect the ability of self-development and increase academic achievement of students is health factors. Well-maintained physical health can spur learning productivity, because a healthy body supports optimal cognitive function. To achieve physical health, a healthy lifestyle is needed. This study aims to analyze the correlation of a healthy lifestyle consisting of diet, physical activity and sleep patterns with students' academic achievement. The research design used is cross-sectional. The study was conducted at the Faculty of Nursing, De La Salle Catholic University, Manado. The population was 280 students of the Nursing Study Program in  2nd  semesters, 4th semesters and 6th semesters. The research sample consisted of 164 respondents. The sampling technique used Purposive Sampling. Data were analyzed univariately and bivariately. The results of this study indicate that there is a relationship between diet and academic achievement (p value: 0.006). It is recommended for students to be able to improve a healthy lifestyle, namely regulating diet, sleep patterns and exercising regularly so that physical health can be maintained and academic achievement can be improved.Keywords: academic achievement, diet, lifestyle, physical activity, sleep patterns.